Bone Morphogenetic Protein Signaling Restricts Proximodistal Extension of the Ventral Fin Fold - Ka, Jun; Kim, Jun-Dae; Pak, Boryeong; Han, Orjin; Choi, Woosoung; Kim, Hwan; Jin, Suk-Won (Frontiers in Cell and Developmental Biology, 2020)
Unpaired fins, which are the most ancient form of locomotory appendages in chordates, had emerged at least 500 million years ago. While it has been suggested that unpaired fins and paired fins share structural similarities, cellular and molecular mechanisms that regulate the outgrowth of the former have not been fully elucidated yet. Using the ventral fin fold in zebrafish as a model, here, we investigate how the outgrowth of the unpaired fin is modulated. We show that Bone Morphogenetic Protein (BMP) signaling restricts extension of the ventral fin fold along the proximodistal axis by modulating diverse aspects of cellular behaviors. We find that lack of BMP signaling, either caused by genetic or chemical manipulation, prolongs the proliferative capacity of epithelial cells and substantially increases the number of cells within the ventral fin fold. In addition, inhibition of BMP signaling attenuates the innate propensity of cell division along the anteroposterior axis and shifts the orientation of cell division toward the proximodistal axis. Moreover, abrogating BMP signaling appears to induce excessive distal migration of cells within the ventral fin fold, and therefore precipitates extension along the proximodistal axis. Taken together, our data suggest that BMP signaling functions as a negative modulator for the outgrowth of the ventral fin fold, illustrating divergent responses toward BMP stimulation in unpaired and paired fins which might reflect their distinct ontogeny during chordate evolution.